Phytoplankton absorption during POLARSTERN cruise ANT-XXVI/4 (PS75) - Astrid Bracher; Bettina B Taylor (PANGAEA, 2021)
Samples were collected during the ANT-XXVI/4 expedition of the RV Polarstern in April/May 2010 along a South-to-North transect through the Atlantic Ocean from Punta Arenas (Chile) to Bremerhaven (Germany) at 32 CTD stations sampling at the surface, chlorophyll max. and 100 depth during noon time and at 57 stations sampling only surface waters through the moonpool of the ship (details see Taylor et al. 2013). Water samples were filtered on GF/F filters, shock-frozen in liquid nitro?gen and stored at -80 C untilel further analysis in the home laboratory. Measurements of the phytoplankton absorption were carried out on a dual-beam UV/VIS spectrophotometer (Cary 4000, Varian Inc.) equipped with a 150 mm integrating sphere (external DRA-900, Varian, Inc. and Labsphere Inc., made from Spectralon (TM)) using a quantitative filterpad technique modified as described in details in Taylor et al. (2011). The data set is also collocated to Bracher (2015) phytoplankton pigment data and Bracher and Taylor (2021) particulate absorption data.